Living with spinal cord injury in Mongolia: A qualitative study on perceived environmental barriers. (3rd July 2020) - Dorjbal, Delgerjargal; Prodinger, Birgit; Zanini, Claudia; Avirmed, Baljinnyam; Stucki, Gerold; Rubinelli, Sara
Abstract : Context : Environmental factors play a key role in the lives of individuals with a spinal cord injury (SCI). This study identifies environmental barriers and their impacts on daily lives as perceived by individuals living with SCI in Mongolia. Design: A qualitative study with semi-structured interviews was conducted. A topic guide for the interviews was structured around the components of the International Classification of Functioning, Disability, and Health. Setting: Urban and rural areas of Mongolia. Participants: A purposive sample of 16 persons with traumatic SCI. Interventions: Not applicable. Outcome Measures: Not applicable. Results: Seven categories of environmental barriers were mentioned, such as poor access to the physical environment, absence of wheelchair-friendly transportation, negative societal attitudes, inadequate health and rehabilitation services, lack of access to assistive devices and medicines, limited financial resources for healthcare, and inaccurate categorization of disabilities in laws. These barriers were claimed to have an impact on physical and psychological health, limit activities, and restrict participation in almost all areas of life. Conclusion: This study contributes to the identification of targets for interventions aimed at improving the lived experience of persons with SCI in a low-resource context. The findings reveal that while the Mongolian government already has laws and policies in place to improve access to the physical environment, transportation, assistive devices and employment, much more has to be done in terms of enforcement. Specialized SCI care and rehabilitation services are highly demanded in Mongolia.